Lie machines : how to save democracy from troll armies, deceitful robots, junk news operations, and political operatives - Howard, Philip N. (Yale University Press, 2020)
Artificially intelligent "bot" accounts attack politicians and public figures on social media. Conspiracy theorists publish junk news sites to promote their outlandish beliefs. Campaigners create fake dating profiles to attract young voters. We live in a world of technologies that misdirect our attention, poison our political conversations, and jeopardize our democracies. With massive amounts of social media and public polling data, and in-depth interviews with political consultants, bot writers, and journalists, Philip N. Howard offers ways to take these "lie machines" apart. Lie Machines is full of riveting behind-the-scenes stories from the world's biggest and most damagingly successful misinformation initiatives--including those used in Brexit and U.S. elections. Howard not only shows how these campaigns evolved from older propaganda operations but also exposes their new powers, gives us insight into their effectiveness, and explains how to shut them down.--